LCA of heavy metals leaching from landfilled sewage sludge ash - Nakić, Domagoj; Vouk, Dražen; Šiljeg, Mario; Bubalo, Anđelina (Journal of Environmental Engineering and Landscape Management, 2021)
Quantities of sewage sludge that are thermally treated (mostly incinerated) are increasing, resulting in growing quantities of sewage sludge ash (SSA) which also requires further management. Despite its potential as a resource, it is still largely landfilled. Considering the presence of potentially toxic and hazardous heavy metals in SSA, this paper analyzes how the change in the leaching concentrations of the selected heavy metals from landfilled SSA impacts the environment (air, water, and soil) by the means of LCA. When considering human toxicity potential as impact category, dominant impacts were due to emissions into the air, primarily caused by leaching of selenium and somewhat less cadmium, mercury and nickel. Mercury had a dominant impact when considering the terrestrial ecotoxicity potential impact. In the SSAs obtained from Croatian sludge, molybdenum leaching, along with selenium and mercury, showed a dominant impact. Therefore, due to the high variability of trace elements, detailed analysis of different SSAs is needed.